By nature, a social animal: an exploration of perceptions of online group work - Hill, Christopher (2023)
This research, exploring the value of online group work through postgraduate student perceptions of engagement, surveyed 71 students and interviewed 11, over three rounds of data collection. Participants were taught postgraduate students in a higher educa tion institution education faculty in the United Arab Emirates. The f indings are relevant for our understanding of online group work; assessment design; communication; and community building. Research took place over a 12-month period, beginning before COVID-19, in February 2020 with face to face teaching, and ending during the third term of fully online teaching in January 2021. This phenomenological research charts student perception and attitude changes. Social Cognitive Theory, the Technology Acceptance Model and Social Constructivism form the theoretical framework within which participant engagement, behaviour and perception are explored. The findings provide a reflective analysis regarding student perception, engagement and acceptance of online group work as a valid approach to meeting learning outcomes.